2018
DOI: 10.1007/s00345-018-2483-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of ProACT primary and repeat implantation for treatment of stress urinary incontinence in men

Abstract: In the hands of an experienced surgeon, ProACT is a safe and effective therapy for post-prostatectomy incontinence especially if mayor surgery is to be avoided. Revision rates are high, but the results of ProACT reimplantation are comparable to the results after the first implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…29 Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al 20 19,30 Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions. 31 For those individuals whose incontinence does not improve with ProACT therapy, this minimally invasive treatment can be easily reversed without hindering implantation of a more invasive therapy, such as AUS.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…29 Higher revision rates for ProACT were shown in papers with longer term follow up. Noordhoff et al 20 19,30 Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions. 31 For those individuals whose incontinence does not improve with ProACT therapy, this minimally invasive treatment can be easily reversed without hindering implantation of a more invasive therapy, such as AUS.…”
Section: Discussionmentioning
confidence: 97%
“…Long‐term failures were primarily attributed to device leakage. Recent studies have shown that the results of reimplantation are comparable to the results after the first implantation . Patients still showed high satisfaction rates even after revisions, demonstrating that patient satisfaction is associated with continence achieved, not with the number of revisions .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Long-term results are very limited with an improvement rate of 45% to 82% of pads per day (PPD) and an improvement of 45% to 74% of quality of life. [15][16][17] Only one study 18 evaluates the efficacy and feasibility of ProACT after a previous sling and persistent SUI. This study analyzed the cumulate experience of our two centers with offering PUB implantation for SUI post-RP in patients with insufficient improvement from slings.…”
Section: Introductionmentioning
confidence: 99%